Re-awakening of GRS 1716-249 after 23 yr, observed by Swift/XRT and NuSTAR - Bharali, Priya; Chandra, Sunil; Chauhan, Jaiverdhan; Garcia, Javier; Roy, Jayashree; Boettcher, Markus; Boruah, Kalyanee (Monthly Notices of the Royal Astronomical Society, 2019)
In this work, we present a spectral and temporal analysis of Swift/XRT and NuSTAR observations of GRS 1716-249 during its recent 2016-2017 outburst. This low-mass X-ray binary underwent an extraordinary outburst after a long quiescence of 23 yr, since its last major outburst in 1993. The source was observed over two different epochs during 2017 April 7 and 10. The best-fitting joint spectral fitting in the energy range 0.5-79.0 keV indicates that the spectrum is best described by relatively cold, weak disc blackbody emission, dominant thermal Comptonization emission, and a relativistically broadened fluorescent iron K alpha emission line. We observed a clear indication of a Compton hump around 30 keV, We also detected an excess feature of 1.3 keV. Assuming a lamp-post geometry of the corona, we constrained the inner disc radius for both observations to 11.92(-11.92)(+8.62) R-ISCO (i.e. an upper limit) and 10.39(-3.02)(+9.51) R-ISCO (where R-ISCO = radius of the innermost stable circular orbit) for the first epoch (El) and second epoch (E2), respectively. A significant (5 sigma) type C quasi-periodic oscillation (QPO) at 1.20 +/- 0.04 Hz is detected for the first time for GRS 1716-249, which drifts to 1.55 +/- 0.04 Hz (6 sigma) at the end of the second observation. The derived spectral and temporal properties show a positive correlation between the QPO frequency and the photon index.
CRIS-Team WoS Importer:2019-08-16